43 The Value of Endoscopic Ultrasound (EUS) in the Investigative Pathway of Acute Idiopathic Pancreatitis (AIP). (28th February 2022) - Bhatti, S.l; Evans, L.; Kumar, B.
Abstract: Introduction: The British Society of Gastroenterology (BSG) guidelines on the management of acute idiopathic pancreatitis (AIP) state the incidence of idiopathic cases to be no more than 30%. However, before a firm diagnosis of AIP is made, Endoscopic Ultrasound (EUS) may be used to determine occult causes. This approach may help prevent recurrent attacks which may evolve into chronic pancreatitis. Method: Retrospective analysis over a one-year period of cases of AIP in a tertiary referral centre was performed to see the incidence of AIP and the role of EUS. Patients with an identifiable cause for pancreatitis were excluded, leaving only those who had received a diagnosis of AIP and the diagnostic value of EUS was examined. Results: Of the 101 patients diagnosed with AIP, 19% (n=19) underwent an EUS successfully. 79% (n=15) had no underlying cause of pancreatitis identified on EUS. In the remaining 21% of cases (n=4), microlithiasis, ductal stones, and pus requiring drainage were common findings. Of these patents, only 1 was referred for surgery. In the patient group with negative findings on EUS, 4% were unaffected, 2% were referred for surgery, 2% died and 7% had recurrent episodes of pancreatitis. Conclusions: The results of this study show that EUS is a valuable modality in patients with suspected AIP, with a positive diagnostic rate of 21%. Therefore, we propose EUS needs to be included in the investigative pathway of all suspected AIP. Although EUS is a relatively scarce resource, further research is required to establish guidelines for the investigation of suspected AIP.